Simultaneous involvement of Brain and Peripheral nerves in a Child with Systemic lupus erythematosus (SLE): A Case Report - Debnath, Bithi (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disorder that affects almost every system in the body. Neuropsychiatric symptoms are common in SLE, but diagnosis often remains difficult. In this case, we report a girl of 16 years who presented with an acute confusional state and features of peripheral neuropathy. A detailed clinical evaluation with a review of the medical history and appropriate laboratory analyses allows this diagnosis to be made. Treatment with immune-modulating therapy, cyclophosphamide resulted in significant improvement of her symptoms. Neuropsychiatric SLE should be considered a potential differential diagnosis for patients presenting with acute confusional state and peripheral neuropathy. J Bangladesh Coll Phys Surg 2025; 43: 89-92